Penguatan Kinerja Pemasaran UMKM: Peran Kepemimpinan Profetik dan Kolaborasi Berbasis Ta'awun Dalam Meningkatkan Adaptivitas Pasar - Bagus A, Wisanggeni; Fatkhurrokhman , Tiyan; Akbar, Tian Khusni; Handoko, Puji (RELIGI: Jurnal Pendidikan Agama Islam, 2025)
Abstract This study examines the influence of prophetic leadership on the marketing performance of Muslim community-based Micro, Small, and Medium Enterprises (MSMEs), with market adaptivity as a mediating variable and ta’awun-based collaboration as a moderating variable. The research is motivated by the challenges of an increasingly dynamic business environment (VUCA) and the need to strengthen marketing agility grounded in Islamic values. A quantitative approach was employed using a survey method involving 150 MSMEs in Central Java, selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM-PLS). The findings reveal that prophetic leadership does not have a direct effect on marketing performance, while market adaptivity also shows no significant influence, thus failing to mediate the relationship. However, prophetic leadership has a positive effect on market adaptivity, and ta’awun-based collaboration significantly moderates the relationship between prophetic leadership and marketing performance. These results highlight the crucial role of Islamic social capital rooted in ta’awun in optimizing prophetic leadership to enhance MSME marketing performance. The study’s implications emphasize the integration of spiritual values and social collaboration into marketing strategies, and it opens opportunities for future research to explore alternative mediating variables such as innovation capability or market sensing capability.